A model of a mathematics editor using intelligent agent technology - Mohd Aris, Teh Noranis; Nazeer, Shahrin Azuan (Elsevier, 2010)
To master the mathematics subject, a lot of exercises need to be done. Mathematical problem solving requires writing mathematics equations and symbols to simplify them to get the answer. A step by step guidance is important to make sure that no mistakes occur. This paper presents a study of existing mathematics editor and proposed a web-based model of a mathematics editor using intelligent agent technology based on the Belief, Desires, Intention (BDI) model. The feature to guide the user step by step is incorporated in the proposed model.